Modeling the relationship between teacher\'s enthusiasm and students\' academic cheating behavior: The mediating role of academic motivation - Masumeh Mirzakhani; Siavash Talepasand; Nemat Sotodeh Asl (مجله علوم روانشناختی, 2023)
Background: Academic cheating behavior is one of the challenging issues in educational environments. This structure has become a global concern in current educational environments and has a significant scope in educational systems. The problem is that the relationships of various variables with academic cheating behavior have been confirmed, but the relationships of variables such as teacher's job enthusiasm and academic motivation have been neglected in the form of structural relationships, and there is a major research gap in this field. Aims: The present study was conducted with the aim of modeling the relationship between teacher's enthusiasm and students' academic cheating behavior with the mediating role of academic motivation. Methods: The method of the present research was applied in terms of purpose and correlational in terms of the nature of the data. The statistical population of the present study included all teachers (N = 1267) and students (N = 2621) of secondary schools in Damghan city in the academic year of 1400-1401. Among the statistical population, 460 teachers (310 women, 150 men) and 460 students (255 girls, 205 boys) were selected by multi-stage random cluster sampling. The teachers responded to the job enthusiasm scale (Schaufeli,2013) and the students responded to the academic motivation scale (vallerand et al,1992) and Academic cheating scale (Murdock & Stephens, 2007). Analysis of research data was done through structural equation modeling with SPSS24 and AMOS26 software. Results: The results of structural equation modeling showed that the data had an acceptable fit with the conceptual model and was confirmed.) RMSEA = 0.065, CFI = 0.90, IFI = 0.90, NFI = 0.91, and X2 /df=2.89). Also, according to the structural model of the research, job enthusiasm had a significant effect on academic motivation (0.34) and academic cheating behavior (-0.21), academic motivation had a significant effect on academic cheating behavior (-0.29). Also, the relationship between job enthusiasm and academic cheating through academic motivation was significant (-0.10) Conclusion: It seems that the results of this research can provide useful information for educational officials, researchers, educational consultants in order to increase teachers' job enthusiasm and reduce students' academic problems.